Kinematic parameters of crawls stroke sprinting through a training season - Minghelli, F.; Castro, F. (Biomechanics and Medicine in Swimming X, 2006)
Swimming velocity (SV) is the product of stroke length (SL) by stroke rate (SR). The purpose of this study was to verify training influence on front crawl SR, SL, SV and stroke index (SI) in sprinting trials. Nine competitive swimmers (7 males and 2 females; age = 14.78 ± 1.48 years) participated. The protocol consisted on the evaluation of SR, SL, SV and SI in a 25 m maximal effort test, every ten weeks, before (M1), during (M2), and after (M3) five months of training. Measurements were obtained from manual counting of cycles and time from 10 to 25 m of the trials. Anthropometric data were collected. Intensity and distance during the training season were controlled. Kinematics data showed stability along the training season. There were improvements (p < 0.05) on anthropometric data throughout the training season. In this age group, anthropometric characteristics seem to be more important than kinematics adaptations due to training for sprinting.